Biological Properties and Molecular Genetic Characteristics of Bacillus Anthracis Strains Isolated During Anthrax Outbreaks in Kazakhstan in 2016 - U. A. Izbanova; L. Yu. Lukhnova; T. V. Meka-Mechenko; E. B. Sansyzbaev; A. D. Kairzhanova; V. B. Shvedyuk; E. Zh. Begimbayeva; V. Yu. Sushchykh; A. B. Shevtsov (Acta Biomedica Scientifica, 2019)
Today, anthrax is recorded in many countries around the world, in Kazakhstan – in the form of sporadic cases or small outbreaks. Despite the endemicity of anthrax in Kazakhstan, the genetic diversity strains is not well described. At the moment, MLVA-25, which is sufficient for molecular and epidemiological monitoring, is recognized as one of the most discriminatory methods of genotyping.Objective: to determine the cultural and morphological properties, the genomic characteristics of the strains of the anthrax pathogen, their geographical distribution in the territory of Kazakhstan during the outbreaks in 2016, a comparative analysis with collection strains isolated since 1962.Methods: microbiological, genetic research methods were used in the work.Results. We investigated 11 strains of B. anthracis, which were isolated in 2016 in Kazakhstan. For comparison of genotypes, 26 strains were used from the collection of pathogenic microorganisms of the A.M. Aykimbaev’s Kazakh Scientific Center for Quarantine and Zoonotic Diseases. Phylogenetic analysis clustered 37 strains of B. anthracis into three clusters and 23 genotypes.The results of studying the phenotypic properties of anthrax strains by the main identification tests showed that all the strains studied in the experiment and isolated from 1961 to 2016 had biological properties characteristic of typical of B. anthracis strains.The anthrax strains isolated in 2016 are characterized as significant variability, as well as the circulation of the same genotypes and clusters in different areas of Kazakhstan. MLVA-profiles of analyzed Kazakhstan strains are unique and do not fully coincide with any studied strain from MLVAbank. On the MST-tree, Kazakhstan’s strains are located in three clusters, as on the phylogenetic tree.Conclusion: Molecular genetic analysis of B. anthracis strains enhances the ability of epidemiologists to track the sources and pathways of infection.It is necessary to improve the tracking system for strains of especially dangerous infections in  Kazakhstan using modern molecular genetic methods.